The Influence of Perceived Value and Repurchase Intention: Study of Generation Z GoSend Consumers in Malang - Arso Tri Handoyo; Nur Laili Fikriah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This study seeks to assess the impact of Perceived Value on the purchase intention of GoSend service users in Malang City. The research methodology employs a quantitative approach, focusing on a community of consumers using GoSend services. The research sample comprised 165 respondents chosen using the Malhotra formula via a nonprobability sampling strategy employing purposive sampling. Data were gathered using an online questionnaire, and the analysis was conducted using SmartPLS software to examine the relationships among variables. The findings indicated that Perceived Value significantly influences Repurchase Intention. This research suggests that users' perceived value significantly influences their motivation to continue utilizing GoSend services. Moreover, elements that affect Perceived Value encompass Application Incentive, Perceived Ubiquity, and Visual Attractiveness. These three factors significantly influence consumer value perception. Incentives like discounts and promotions substantially enhance perceived value, emphasizing consumers' need for appealing promotional techniques. Perceived Ubiquity, indicative of the accessibility of services at any time and location, significantly impacted Perceived Value, underscoring the relevance of service flexibility for consumers. Moreover, the application's visual appeal, including an aesthetically pleasing UI and intuitive navigation, emerged as a critical determinant in fostering a favorable opinion of service value. This study offers strategic insights for GoSend to enhance client loyalty. Organizations can enhance Perceived Value by refining incentive programs, augmenting service flexibility, and guaranteeing an appealing, user-friendly application design. This study underscores the significance of cultivating and sustaining a favorable perception of value to promote repurchase intentions among delivery service consumers, particularly within the Generation Z demographic.